Correlation of Vitamin D and Body Mass Index in Term Normotensive and Pre -Eclamptic Women - Gupta, Taru; Gupta, Nupur; Wadhwa, Leena; Arora, Sarika; Bagla, Jyoti; Wahi, Sonika (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Obesity is associated with alteration in the vitamin D levels and has been related to vitamin D status. Lower vitamin D levels in higher BMI individuals may be secondary to an alteration in tissue distribution resulting from an increase in adipose mass. Therefore women with higher BMI need higher vitamin D supplementation as compared to women with BMI within normal range. MATERIAL AND METHOD: This was a case control study carried out in Department of Obstetrics and Gynaecology, ESIC-PGIMSR, New Delhi from August 2012-April 2014. A total of 100 patients were divided into two equal groups (control and study groups of 50 each). Control group had women with singleton uncomplicated term normotensive pregnant women in labour while the study group comprised of term preeclamptic women in labour.In all the patients their BMI was analysed .Blood samples for vitamin D, serum calcium, serum phosphorus, serum parathormone, serum alkaline phosphatase levels were drawn and subsequently their levels were evaluated in cord blood; correlation studied between vitamin D & BMI. RESULTS: The mean BMI was relatively higher in the study group (26.34 ± 4.12)kg/m2 than in the control group ( 24.24 ± 3.13)kg/m2. Thus in our study a prevalence of higher BMI was seen in patients of preeclampsia. When all the 100 women are being considered, median vitamin D levels were found to be higher (6.6ng/ml) in normal BMI patients (n=55) as compared to levels (5.6ng/ml) in patients with higher BMI(n=45). CONCLUSION: Vitamin D levels are related to maternal body mass index. Individuals with higher percentage body fat may require higher vitamin D intake to attain optimal 25(OH) D levels, compared with lean individuals and thereby may prevent pregnancy complications like Pre eclampsia.